Comparative Performance Evaluation for Jebba, Kainji and Shiroro Hydro Power Schemes - Maruf A. Aminu; Garba U. Kangiwa (Archives of Current Research International, 2019)
This paper evaluates performance indices based on industry-wide practice and suggests possible approach for improving the operational efficiencies of Jebba, Kainji and Shiroro hydro power generating stations. To actualize that, data including average daily gross operating head, daily flow rate and daily energy generated were obtained from Jebba, Kainji and Shiroro power stations and the National Control Center (N.C.C.) Osogbo. From the energy (MWh) generated the average daily power generated (MW) was computed. Consequently, the average operational efficiencies of Jebba, Kainji and Shiroro hydro schemes were evaluated and found to be 89.43%, 88.45% and 94.03% respectively. Similarly, performance indicators including deemed generation, auxiliary energy consumption, availability factor, capacity index, workforce deployment, forced outage factor and scheduled outage factor were evaluated and technical inferences made. The study was limited to the year 2010 due to non-availability of data for other years.